2022
DOI: 10.3390/polym14061157
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Rigid Polyurethane Foams Incorporating Polyols from Chemical Recycling of Post-Industrial Waste Polyurethane Foams

Abstract: The preparation and characteristics of rigid polyurethane foams (RPUFs) synthesized from polyols obtained by glycolysis of post-industrial waste RPUFs have been studied. More precisely, waste rigid foams that have been chemically recycled by glycolysis in this work are industrially produced pieces for housing and bracket applications. The glycolysis products have been purified by vacuum distillation. The physicochemical properties of the polyols, such as hydroxyl value, acid value, average molecular weight (Mn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Alkali metal hydroxides and organic/inorganic metal salts are common catalysts for glycolysis. For example, addition of sodium hydroxide (NaOH), sodium acetate (NaOAc), or iron chloride (FeCl 3 ) improved both rate and conversion of glycolysis with EG. , With the addition of a catalyst, glycolysis with EG reached 90% conversion within 1 h, while without a catalyst glycolysis was limited to 80% overall conversion after 5 h. The addition of a potassium octoate catalyst to the glycolysis of PU with DEG expedited the kinetics to a rate comparable to that observed with EG which increased the yield of repolyol to 80%, compared to 40% without a catalyst . Furthermore, Maioli et al demonstrated glycolysis of PU assisted by ionic liquids, giving 70% yield of repolyol in DEG or glycerol medium with 1-butyl-3-methylimidazole trichloromanganate or 1-butyl-3-methylimidazole trichlorozincate catalysts .…”
Section: Chemical Recycling Methodsmentioning
confidence: 99%
“…Alkali metal hydroxides and organic/inorganic metal salts are common catalysts for glycolysis. For example, addition of sodium hydroxide (NaOH), sodium acetate (NaOAc), or iron chloride (FeCl 3 ) improved both rate and conversion of glycolysis with EG. , With the addition of a catalyst, glycolysis with EG reached 90% conversion within 1 h, while without a catalyst glycolysis was limited to 80% overall conversion after 5 h. The addition of a potassium octoate catalyst to the glycolysis of PU with DEG expedited the kinetics to a rate comparable to that observed with EG which increased the yield of repolyol to 80%, compared to 40% without a catalyst . Furthermore, Maioli et al demonstrated glycolysis of PU assisted by ionic liquids, giving 70% yield of repolyol in DEG or glycerol medium with 1-butyl-3-methylimidazole trichloromanganate or 1-butyl-3-methylimidazole trichlorozincate catalysts .…”
Section: Chemical Recycling Methodsmentioning
confidence: 99%
“…In a further research effort, Amundarain and co-workers 133 exploited the polyols, recovered from post-industrial rigid polyurethane foams by means of glycolysis reactions, for preparing new rigid foams. The recovered counterparts showed remarkably higher values for viscosity, acidity, and average molecular weight and more hydroxyl groups than those of commercial polyols: these findings were ascribed to both the residual ethylene glycol in the polyol after the purification of the glycolysate and in the presence of glycolysis by-products (such as amines and carbamates).…”
Section: Recent Advances In Polyurethane Recyclingmentioning
confidence: 99%
“…However, there is a lack of scientific publications regarding the lifespan of PUFs where their mechanical properties are relevant, such as sandwich panels [ 6 ]. Many studies regarding the synthesis, characterizations and applications of bio-based PUFs are being carried out every year due to its pairing characteristics with oil-based foams as well as its relative low cost and eco-friendly origin [ 7 , 8 , 9 , 10 ]. PUF is a two-phase material composed of a continuous polymer matrix and the gas in the discretely distributed cells.…”
Section: Introductionmentioning
confidence: 99%